Enhancing Online STEM Education: Impacts of Pre-Released Exam Materials and Remote Proctoring - Meta Landys (Online Learning, 2025)
Undergraduate STEM courses commonly evaluate students using timed, high-stakes “traditional” exams. However, the use of such exams may harm cognitive development, attitudes of students toward their discipline, and various categories relating to motivation. Also, implementation of such traditional exams may perpetuate demographic achievement gaps. I hypothesized that the pre-release of exam materials could address such concerns. To this end, I examined the effect of pre-released exam materials on broad student outcomes in a distance education biology course, paying attention to exam performance, attitudes towards the discipline, and various motivational components related to learning. I found that in comparison to a traditional exam system, the pre-release of exam materials did not improve exam performance, attitudes, or motivation of online biology students. Also, pre-released exams did not rescue the achievement gap associated with lower socioeconomic status (SES). Nevertheless, qualitative responses of students to an open-ended survey indicated that pre-released exams offered a unique experience – with reduced anxiety as a major benefit. These data suggest that a pre-released exam system could be utilized to decrease test-taking anxiety in online STEM courses, without exacerbating SES-related achievement gaps. In fact, the pre-release of exam information may increase the authenticity of exams, as it mirrors work in real-life STEM careers. In parallel to the above, I found that remote online proctoring requirements imposed penalties on student exam performance, but maintained favorable attitudes toward the discipline. This suggests that the impact of remote proctors for online STEM students should be more carefully considered.